Assessment of bacterial load in broiler chicken meat from the retail meat shops in Chitwan, Nepal - Bhandari, N; Nepali, DB; Paudyal, S (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Keeping quality of meat and meat related food hazard relates to microbes present in the meat during processing or storage. The poultry slaughtered and dressed under Chitwan conditions carrying high initial contamination would be present in meat as inherent contamination in the finished products. MATERIALS AND METHODS: This cross-sectional study included 26 fresh broiler meat samples from registered retail shops. The samples were subjected to bacteriological analysis such as total viable count (TVC), total enterobacteriaceae count (TEC), total coliform count (TCC) and total staphylococcal count (TSC). Also, the samples were analyzed for the detection of Salmonella spp. and identified by different biochemical tests. RESULTS: The mean counts in log10±SE colony forming units per gram (cfu/g) for Bharatpur, Ratnanagar and Institute of Agriculture and Animal Science (IAAS) vicinity were obtained as 11.1±0.3, 11.5±0.3 and 12.2±0.5 TVC; 8.5±0.2, 9.2±0.3 and 10.2±0.4 TEC; 6.5±0.3, 7.6±0.3 and 8.4±0.5 TCC; 6.5±0.2, 6.8±0.3 and 7.7±0.4 TSC respectively. No samples were found to be within the permissible limits given by different agencies. Prevalence of Salmonella spp. in retail broiler meat in Chitwan was found 46.2%. CONCLUSION: The retail broiler meat samples from the locations contain high count of bacteria suggesting deplorable state of hygienic and sanitary practices. The presence of Salmonella and Staphyloccus aureus organisms over the permissible limits are of special concern because these account for potential food borne intoxication. So, the need for microbial assessment of fresh meats can be emphasized. DOI: http://dx.doi.org/10.3126/ijim.v2i3.8671 Int J Infect Microbiol 2013;2(3):99-104